Future climate change would intensify the water resources supply-demand pressure of afforestation in inner Mongolia, China. (25th June 2023) - Wang, Ziyu; Xu, Duanyang; Peng, Daoli; Zhang, Xiaoyu
Abstract: As a vital solution for combating the environmental degradation, afforestation has been widely implemented in arid and semi-arid areas. However, some negative effects have also occurred, due to the lack of regional water resources. Besides, with the impact of climate change, water scarcity in these areas is likely to get worse in the future. In this study, the water resources supply-demand pressure of afforestation under different future scenarios in Inner Mongolia was investigated. Landtrendr method was used to detect the increased vegetation area from 2000 to 2020, and the afforestation area was identified by overlapping analysis combined with the land cover data. The water stress index (WSI) was employed to analyze the water pressure of afforestation area. The results revealed four major findings. (1) During 2000–2020, the accumulated afforestation in Inner Mongolia was 71410 km 2, and the shrubs accounted for 86% of the total area of afforestation; (2) The afforestation water stress index showed a significant upward trend with mean values of 0.55, 0.59 and 0.61 under RCP 2.6, 4.5 and 8.5 scenarios, respectively; (3) The overall water resources supply-demand pressure of afforestation in the western region was greater than that in the eastern of Inner Mongolia. (4) In the future, measures need to be taken to alleviate the pressure of water resources on the afforestation in western Inner Mongolia. These findings could help us figure out the afforestation water stress under the climate change and provide the reference to adopt reasonable afforestation management strategies. Highlights: Afforestation area increased by 71410 km 2 in Inner Mongolia, from 2000 to 2020. The afforestation water resources pressure was higher in western Inner Mongolia. The water resources supply-demand pressure increased with higher CO2 emissions.